Penelope Heynes' Full Stroke at 160 m of Her 200 m Breaststroke Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S. (1999)
Video pictures (14 frames) and the appropriate technical/ biomechanical explanations for Penelope Heynes' Full Stroke at 160 m of Her 200 m Breaststroke Gold Medal Race at the Atlanta Olympic Games 1996.